Microstructure and mechanical properties of porous copper and copper brazed with cu-based filler metal / Mian Muhammad Sami - Mian, Muhammad Sami (2021)
In recent time, the heat dissipation rate of electronics increased due to the high volumetric power density they experience. In such circumstances, cooling devices with high heat transfer performance are required. Therefore, adopting porous metal can be critical in applications requiring thermal management due to its large internal surface area and high permeability for fluids. The cooling system can be composed of porous copper to enhance heat transfer making it suitable for replacement in active cooling systems, such as heat sink and heat exchanger. Effective joining of porous copper (Cu) to a copper substrate is significant when considering porous copper in the design of active cooling systems. In this research, brazing is conducted to join porous copper to a copper substrate using one piece of filler metal placed at the base side to join the base and the top side. Only one piece of filler is used to prevent the brazing material from entirely filling the cells. This method of joining two sides of metal using a single piece of filler metal with porous copper in the middle has not been studied previously. The influence of brazing parameters on the microstructural and mechanical properties of copper brazed with porous copper using amorphous filler metal (Cu-9.7Sn-5.7Ni-7P) is investigated. Brazing was done in a tube furnace equipped with a heating controller and argon gas. The brazing temperatures used in this experiment were 660 °C, 680 °C and 700 °C. The holding time was 5, 10 and 15 min. After brazing, the microstructure characterization was performed using Scanning Electron Microscope equipped with Electron Dispersive X-ray Spectroscope. To confirm the microstructure results, further analysis was conducted with X-Ray Diffractometer. It was observed that, after increasing holding time and temperature, voids or cracks were not visible in the overall bonded region. High diffusion of filler metal was also observed at porous copper surface. The diffusion between copper (Cu), nickel (Ni), tin (Sn) and phosphorus (P) created strong interactions. The EDS analysis revealed that phosphorus and nickel were iv the main elements contributing to the microstructure formation. The microstructure of the brazed joints changed with increasing holding time and the diffusion of P-rich and Ni-rich phases to the upper side of the joint was observed. The element Sn completely diffused from the bonding area into the base metal due to the lower melting temperature. A further analysis was conducted to investigate the mechanical properties of porous copper and joint interface by conducting hardness and compression tests. The phases formed reduced the ductility of copper due to surface hardening effects at the brazed joint interface and porous copper. It was noticed that the rigidity of porous copper increases with increasing holding time and temperature. This is due to the diffusion of elements from the brazing filler metal into the porous copper surface. The rigidity of porous copper after brazing is vital to ensure minimal deformation of porous copper during cooling device servicing, an integral feature of prospect product development.